Caracterização da postura, tônus e mobilidade de lábios e língua em crianças respiradoras orais - Schmidt, Rafaela (2010)
Introduction: nasal breathing is an essential function to assure a balanced growth and development of the orofacial muscles. Aim: to characterize the posture, tone and mobility of lips and tongue of mouth breathing children. Methods: the subjects of this study were 40 mouth breathing children, 26 boys and 14 girls. All subjects were submitted to an evaluation of posture, tone and mobility of the lips and tongue, using the MBGR protocol. Results: for the lips posture variable, it has been observed that: 32.5% of the subjects had a semi-open lip posture, 27.5% alternate between open and closed lips, 22.5% had an open lip posture and just 17.5% maintained their lips closed. With regards to the upper lip tone: 90% presented normal muscle tone, 10% lower tone, and no subjects presented a higher muscle tone. As for the tone of the lower lip 80.0% of the children presented lower muscle tone, and 20.0% normal muscle tone. For the lips mobility variable 47.5% of the group presented normal score values and 50.0% scored close to normality. Regarding tongue posture, 57.5% of the children had a low-lying resting tongue posture, 32.5% did not allow for observation of this variable, and in 10.0% of the subjects the tongue was placed in an interdental resting posture. As for tongue muscle tone 52.5% presented lowered tone, and 47.5% were considered normal. When assessing tongue mobility, 55.0% of the children obtained the best results and 45.0% had score values very close to the best. Conclusion: according to the results for the majority of the assessed mouth breathing children, the following characteristics were found regarding the lips: semi-opened posture, upper lip with normal tone, lower lip with lowered tonicity and normal mobility. The following results were found regarding the tongue: low-lying resting posture, with lowered muscle tone and normal mobility